Metode Imputasi pada Data Debit Daerah Aliran Sungai Opak, Provinsi DI Yogyakarta - Fahmi Dhimas Irnawan; Indriana Hidayah; Lukito Edi Nugroho (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2021)
The data availability of water resources in Indonesia has several complex problems related to the perfection of data. The problems taking place when collecting data in several Indonesian agencies are the accuracy and completeness of the data. There are several methods that can be used to handle missing value imputation, such as k-Nearest Neighbors Imputation (k-NNi) and Multivariate Imputation by Chained Equation (MICE). This study seeks to compare and find the most appropriate method using the Opak watershed dataset in Special Region of Yogyakarta. The characteristics of the Opak watershed lies in its fan shape that provides a lower concentration-time and produces a higher flow. The results of the statistical validation comparison showed that the most consistent average value of RMSE and MAE was the k-NNi method with a value of k = 28. As for the comparison of R-Squared values, the k-NNi method with a value of k = 28 obtained the best average value with 80%, followed by the k-NNi method of k = 7 as the default k value with a percentage of 73%. Among the applied methods, the MICE comparison method obtained the lowest average percentage value with 63%.